An overview and comparison of supervised data mining techniques for student exam performance prediction - Tomasevic, Nikola; Gvozdenovic, Nikola; Vranes, Sanja (Computers and education, 2020)
Recent increase in the availability of learning data has given educational data mining an importance and momentum, in order to better understand and optimize the learning process and environments in which it occurs. The aim of this paper is to provide a comprehensive analysis and comparison of state of the art supervised machine learning techniques applied for solving the task of student exam performance prediction, i.e. discovering students at a “high risk” of dropping out from the course, and predicting their future achievements, such as for instance, the final exam scores. For both classification and regression tasks, the overall highest precision was obtained with artificial neural networks by feeding the student engagement data and past performance data, while the usage of demographic data did not show significant influence on the precision of predictions. To exploit the full potential of the student exam performance prediction, it was concluded that adequate data acquisition functionalities and the student interaction with the learning environment is a prerequisite to ensure sufficient amount of data for analysis. •Overview of state of the art machine learning techniques in the context of student performance prediction.•Comparison of performance trends and computational requirements of analysed machine learning techniques.•Identification of optimal input data sets for optimisation of particular machine learning technique.•Artificial Neural Networks showed overall best results for solving student performance prediction tasks.